Light-Induced Cytochrome c Redox Mediated Cell Killing - Potts, Jordan Cameron (2023)
This research presents a novel cancer treatment strategy employing gold nanoparticles as Cytochrome c carriers. Leveraging the protein's inherent apoptotic capabilities, this approach activates the therapeutic potential of Cytochrome c using a porphyrin "trigger" when exposed to monochromatic visible light. This research meticulously details the synthesis, functionalisation, and characterisation of AuNPs with diameters of 20, 50, and 100 nm, utilising many analytical techniques. The AuNPs were functionalised with Cyt c and Zn Porph through two distinct ligands and conjugation strategies, preserving their stability. Our novel spectral deconvolution approach critically ascertains the precise concentration and number of conjugated molecules on AuNPs, setting the stage for an in-depth analysis of their impact, primarily on the redox capabilities of Cyt c. The core objective was to determine if conjugated Cyt c and Zn Porph can instigate apoptosis in cancer cells upon exposure to light.